Kingdom Animalia, phylum Annelida (bristleworms & kin) - Read, Geoffrey B. (NIWA Biodiversity Memoir, 2023)
Phylum Annelida now includes members of the former phyla Sipuncula, Echiura, and Pogonophora, plus the Clitellata (leeches and oligochaetes), which are downranked into the Polychaeta, largely as a result of DNA evidence. The total number of described, and known but undescribed, extant marine annelid species, from the Aotearoa New Zealand region is 928 marine Annelida, including 606 described species and 322 undescribed entities (Table 18.1; Figs 18.1-18.3). This is an increase of 100 marine Annelida names from 2009 (Cutler 2009a, b; Glasby et al. 2009). Since the original inventories of Cutler (2009a, b) and Glasby et al. (2009) on the Sipuncula, Echiura, and Annelida there are 49 additional taxa with published records for New Zealand, but only 10 of these are newly described species. No additional fossils have been named to species subsequent to Hayward (1977). The state of knowledge of New Zealand Annelida is discussed, the future outlook explored, and problem non-indigenous species are noted. A checklist of extant and fossil New Zealand Annelida is provided and discussed
Annelidabase. Includes Excel augmented checklist. The complete memoir is at: https://niwa.co.nz/oceans/niwa-biodiversity-memoir-136-marine-biota-aotearoa-new-zealand